2012
DOI: 10.1016/j.juro.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

MYC Copy Number Gains are Associated with Poor Outcome in Penile Squamous Cell Carcinoma

Abstract: MYC gains progressively increased during penile squamous cell carcinoma progression from in situ samples to metastases. MYC gains were an independent factor for poor prognosis. These findings were independent of HPV infection. MYC expression was increased in samples with HPV infection, probably reflecting direct activation of MYC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…A previous study by our group in this patient series demonstrated an association between HPV and a better prognosis in PSCC. 4 Statistical correlation between HPV and a better outcome was also reported for vulvar cancer. 21 According to Rodrigues et al HPV related vulvar tumors do not seem to undergo an EMT phenomenon, which is commonly associated with a worse cancer prognosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A previous study by our group in this patient series demonstrated an association between HPV and a better prognosis in PSCC. 4 Statistical correlation between HPV and a better outcome was also reported for vulvar cancer. 21 According to Rodrigues et al HPV related vulvar tumors do not seem to undergo an EMT phenomenon, which is commonly associated with a worse cancer prognosis.…”
Section: Discussionmentioning
confidence: 90%
“…3 The rate of HPV identification in PSCC varies from 15% to 77.5% depending on the technique, the study population and/or the subtype. 4 High risk HPV16 is by far the most frequently detected genotype in PSCC. In contrast to cervical cancer, in which HPV is found in 100% of cases, HPV related lesions are more common in some PSCC subsets, such as the basaloid and warty subtypes.…”
mentioning
confidence: 99%
“…MYC is a transcription factor responsible for the regulation of approximately 15% of the human gene set, acting in processes such as cell growth and proliferation, cell-cycle progression, transcription, differentiation, apoptosis, and cell motility (28). Previously, MYC gains or amplification, as well as increased gene and protein expression related and unrelated to HPV positivity, were described in penile carcinomas (5,29). It was reported that MYC activation was mediated by viral integration, which may be an important event in penile oncogenesis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Circumcision in childhood has clearly been shown as a protective factor to minimize this risk of penile cancer. Furthermore, the higher viral infection rate within uncircumcised males could explain the cancer preventative impact of circumcision independent from its underlying mechanism of minimizing chronic inflammation [11]. Since early sexual contacts, promiscuity, and oral sexual practices are also known risk factors for penile cancer, the potential role of viral infection in inducing carcinogenesis seems quite biologically plausible [9].…”
Section: Molecular Mechanisms Of Penile Cancer Progressionmentioning
confidence: 99%